Examining the Effect of Fatherlessness on Students’ Mathematical Mindset - Meita Sari; Eka Fitria Ningsih; Ferdian Utama; Fathma Salsabila; Lilin Nailul Fauziah; Santi Widyawati (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to examine the relationship between fatherlessness and mathematical mindset through self-esteem. The study used an ex post facto correlational research design involving 184 junior high school students. The instruments used were the fatherlessness scale, self-esteem scale, and mathematical mindset scale, all of which had been tested for validity and reliability. Data analysis was performed using Andrew F. Hayes' Process Model 4. The results showed that fatherlessness had a significant negative effect on self-esteem (β=-0.298, p<0.01). Self-esteem had a positive effect on mathematical mindset (β=0.384, p<0.01), and fatherlessness also had a direct negative effect on mathematical mindset (β=-0.167, p<0.01). In addition, there is an indirect mediating effect through self-esteem (β=-0.114, 95% CI [-0.184, -0.062]). The implications of the research results for guidance and counseling practices will be discussed.